Enhancing Teachers’ Professionalism and Students’ Learning Outcomes through Lesson Study - Areni, Galuh Kirana Dwi; Syafri, Frimadhona (Universitas Negeri Semarang, 2018)
In this study, the writer as a teacher model, tried to explore: (1) the advantages and disadvantages of lesson study applied in a theoretical subject class; and (2) the effectiveness of it for students' learning outcomes. It was conducted in a class called Introduction to Linguistics with 30 students. There were four cycles and four colleagues who took part as the observers. In each cycle, she did PLAN, DO, and SEE. Then, descriptive analysis was used to elaborate teachers‘ professionalism and students‘ learning outcomes through observation sheets, discussion, and test. The result shows that there are some benefits, i.e. (1) the teacher can prepare her lesson plans and teaching media more carefully; (2) she can conduct her class more confidently and professionally; (3) she can get evaluation about her teaching process after her class ends; (4) the students can be more active and study more seriously; and(5) they can achieve better scores compared to other classes which don‘t use lesson study. However, there are also some disadvantages, e.g. (1) the teacher needs more time to prepare her lesson plans and teaching media; and (2) some students may feel depressed because of the observers‘ attendance.